Model Pengembangan Kompetensi Sosial Kultural Aparatur Sipil Negara (ASN) Pada Unit Pelaksana Pelayanan Terpadu Satu Pintu (UPPTSP) Di Kecamatan Kembangan Jakarta Barat - Sutrisno, Edy; Simangunsong, Tinawati (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2021)
This study aims to determine how the socio-cultural competence of apparatus resources in the One-Stop Integrated Service Implementation Unit of Kembangan District. Each Apparatus Resource is required to have three competencies, technical competence, managerial competence and social cultural competency. As a service provider who is directly dealing with the community, socio-cultural competence is needed by every service provider officer. Competency development carried out at this time more development of technical competencies and managerial competencies, so in this study the author tries to develop a model for developing the socio-cultural competence of apparatus resources in the PTSP Implementation Unit of Kembangan District. In this study a Social Cultural Competency Development Model was formed which can be implemented internally (implemented by UP PTSP Kembangan District and carried out externally (implemented by BPSDM DKI Jakarta Province) .The internal development model is in the form of personal approach, coaching, briefing, gathering, benchmarking, personnel development (self-development), while external development is carried out in the form of service orientation, education and training services for persons with disabilities, communication education, ASN exchanges with private employees, competency tests and competency test feedback.